Problem of Bureaucratic Rationality : Tax Politics in Japan - Kato, Junko, 1961- (Princeton University Press, 2001)
Through a detailed account of the political battles over Japanese tax reform during the last two decades, Junko Kato draws an unconventional portrait of bureaucratic motivation, showing how fiscal bureaucrats exploit their unique technical knowledge to influence policymaking. Rejecting the notion that the monopolization of policy expertise leads to bureaucratic domination, Kato contends that bureaucrats seek to increase their influence upon politicians by strategically sharing information. She also explores the reason for the relative strength of the bureaucratic organization in comparison to the governing party, whose interest in reelections and intra-party politics may pose dilemmas for individual politicians.